ENTREPRENEURSHIP AS AN EDUCATIONPROFESSIONAL PATHWAY DIRECTION FOR PROFESSIONAL (VOCATIONAL) EDUCATION SCHOOLS STUDENTS - Закатнов, Дмитро (Naukovij vìsnik Ìnstitutu profesìjno-tehnìčnoï osvìti NAPN Ukraïni. Profesìjna pedagogìka (Online), 2019)
The article reveals the state-of arts of the problem on professional (vocational) education (P(V)E) schools students training to choosing the entrepreneurship activity as the way for further professional career development. It is found that the entrepreneurship activity content in the legislation framework of Ukraine is limited with acts jure gestionis aimed at reaching the economy and social results and profit. That differs from the appropriate content in the EU countries where the entrepreneurship is defined as the ability to plan and manage projects with have cultural, social or commercial value. The analysis the pilot research empirical data and the experimental activity of the Institute of vocational education and training of the National academy of educational science of Ukraine (IVET NAES of Ukraine) proves that P(V)E schools students consider the entrepreneurship activity as a prospective vector for further education-professional rout realisation due to some indicators difference for urban and rural P(V)E schools students. Therefore, the students’ vision of the entrepreneurship activity is mostly of abstract character but their training to that in P(V)E schools is provided only for some aspects. The entrepreneurship activity socio-economic value and attractiveness for the youth as a prospective vector for their education-professional routs are determined with the appropriate pedagogical system formation to assure students’ preparation for the entrepreneurship activity.